TECHNOLOY DEVELOPMENT FOR STRONG REDUCTION OF ENERGY CONSUMPTION AND CO2 EMISSION IN LIME AND CEMENT MANUFACTURE - Villachica, Carlos; Villachica, Joyce (GeoScience Engineering, 2017)
Cement and lime industry are responsible for 8% of global CO2 emission; 35% of CO2 comes from fuel combustion to heat and decompose limestone and form lime or “clinker” in open atmosphere while the remaining 65% comes from limestone rock itself. High grade of both Lime and CO2 were obtained faster and at much lower than conventional temperatures and CO2 fully captured and utilized when using an HEVA reactor for limestone Calcination. Clinker, a precursory of cement, was partly obtained at lower temperature when starting from HEVA lime and fine quartz after mechanochemical pretreatment.